A Network Coding-Based Braided Multipath Routing Protocol for Wireless Sensor Networks - Li, Zhihua; Xu, Minda; Liu, Tingxu; Yu, Lei (Wireless Communications and Mobile Computing, 2019)
In wireless sensor networks (WSNs), energy efficiency can simultaneously guarantee robustness to link loss and node failure and is a key design goal of routing protocols because WSNs are strongly constrained in terms of transmission reliability, transmission delay, and energy consumption. Braided multipath routing has become a powerful tool for tolerating node failures and link losses, with high reliability and efficient data transmission rates. In this paper, we propose a novel network coding-based braided multipath routing called NC-BMR protocol. It integrates a data compression-based network coding method with the construction of hierarchical multiparent nodes (HMPNs) topology for the routing with coordinated data forwarding manner and a multipackets-based time scheduler strategy (MTSS). Its perfect transmission efficiency is achieved by only attaching a little control information with data packets. We validated NC-BMR based on the TOSSIM platform and compared it to several previous methods. Theoretical analysis and simulation results demonstrate its performance improvement in terms of the transmission reliability, delay, and overhead.